1961
DOI: 10.1042/bj0790209
|View full text |Cite
|
Sign up to set email alerts
|

Observations on the metabolism of tyrosine O[35S]-sulphate in the rat

Abstract: Arylsulphate esters are normally present in appreciable amounts in mammalian urine where

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1962
1962
1977
1977

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…was subjected to paper chromatography showed that the mobility of the unknown metabolite (R, 028, see Dodgson et al 1961) corresponded to that of the authentic sample of p-hydroxyphenylpyruvic acid [35S]-sulphate when the latter was chromatographed in the presence of normal rat urine. A similar agreement was obtained between electrophoretic mobility of metabolite and authentic sample.…”
Section: Experimental and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…was subjected to paper chromatography showed that the mobility of the unknown metabolite (R, 028, see Dodgson et al 1961) corresponded to that of the authentic sample of p-hydroxyphenylpyruvic acid [35S]-sulphate when the latter was chromatographed in the presence of normal rat urine. A similar agreement was obtained between electrophoretic mobility of metabolite and authentic sample.…”
Section: Experimental and Resultsmentioning
confidence: 99%
“…The disappearance of the metabolite from solution B was then followed by measuring the keto-enol difference spectrum ( Subsequently, solutions A and B were subjected to paper chromatography together with a portion of the original urine that had been freeze-dried immediately after collection. The Dodgson et al 1961). …”
Section: Experimental and Resultsmentioning
confidence: 99%
See 3 more Smart Citations